Starburst and old stellar populations in the z -~ 3.8 radio galaxies 4c 41.17 and TN J2007-1316 - Rocca-Volmerange, B.; Drouart, G.; De Breuck, C.; Vernet, J.; Seymour, Nick; Wylezalek, D.; Lehnert, M.; Nesvadba, N.; Fioc, M. (2013)
Using the new evolutionary code Pégase.3, we undertook an evolutionary spectral synthesis of the optical–IR–submm spectral energy distribution of two distant (z = 3.8) radio galaxies, 4C 41.17 and TN J2007−1316. These two radio galaxies were selected from the HeRGÉ (Herschel Radio Galaxies Evolution) Project in particular for their faint active galactic nucleus contribution and because they show evidence of a large stellar contribution to their bolometric luminosity. Pégase.3 coherently models the reprocessing of the stellar luminosity to dust emission, allowing us to build UV to IR–submm spectral energy distribution libraries that can then be used to fit spectral energy distributions in the observer's frame. Our principal conclusion is that a single stellar population is insufficient to fit the spectral energy distribution of either radio galaxy. Our best fits are a sum of two evolving stellar populations – a recent starburst plus an old population – plus the thermal emission from an active galactic nucleus (which provides a good fit to the mid-IR emission). The two stellar components are: (i) a massive -~ 1011  M☉) starburst -~30 Myr after formation, which is required simultaneously to fit the far-IR Herschel to submm data and the optical data; and (ii) an older massive (-~ 1011–12  M☉) early-type galaxy population,-~1.0 Gyr old, which is required principally to fit the mid-IR Spitzer/IRAC data.A young population alone is insufficient because an evolved giant star population produces a 1-μm rest-frame peak that is observed in the IRAC photometry. This discovery confirms that many of the stellar populations in high-redshift radio galaxies were formed by massive starbursts in the early Universe. Gas-rich mergers and/or jet–cloud interactions are favoured for triggering the intense star formation necessary to explain the properties of the spectral energy distributions. The discovery of similar characteristics in two distant radio galaxies suggests that multiple stellar populations, one old and one young, may be a generic feature of the luminous infrared radio galaxy population.